Plant vs. Animal, Which is the Most Prefer Understanding of Evolution? - Hana Gardenia Mahbubah; Topik Hidayat; Bambang Supriatno (International Journal of Science and Applied Science: Conference Series, 2017)
Evolution is one of the main subjects of biology taught in science colleges. Unfortunately, students seem less attention to this subject. In the subject of evolution, the lesson commonly uses the animal as a model to improve the students understanding. The purpose of this study is to compare the ability of tree thinking students who use animals and plants as a model in the evolution lesson. Tree thinking refers to an approach to evolution that emphasizes reading and interpreting phylogenetic tree. This study involved 20 undergraduate students enrolled in the evolution course for biology majors at Universitas Pendidikan Indonesia (UPI). The tree thinking ability of students was measured using Tree Thinking Concept Inventory (TTCI) of Naegle with a little modification. In this test, we analyzed student preferences using animal or plant models using phylogenetic tree diagrams. Results showed that students’ TTCI score was higher when using animal models (65.42%) than plant models (55%). These results suggested that students remain to prefer animal models compare to plant models to study evolution. Nevertheless, the use of plants as models can be an alternative to learning evolution in the future.